Corporate Governance Strength, Firm’s Characteristics, and Islamic Social Report: Evidence from Jakarta Islamic Index - Wahyono Wahyono; Eskasari Putri; Bayu Tri Cahya (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: The purpose of this study is to analyze the effect of corporate governance strength, company size, profitability, company age, and industry type on Islamic social reports of Indonesian Companies that are listed in Jakarta Islamic Index.Design/Methodology/Approach: The type of data used in this study was secondary data in the form of quantitative data, which included annual financial statements data completed with auditor’s reports from each company listen on JII, especially in 2015-2017. The sampling method used in the study was purposive sampling.Research findings: The results of data processed employing multiple regression test showed that company size, company age, and type of industry had a significant effect on the disclosure of Islamic social reporting. Corporate social strength and profitability had no significant effect on disclosure of Islamic social reporting.Theoretical contribution/Originality: This research has theoretical implications in terms of developing knowledge and confirming theories about Islamic social reporting in IndonesiaPractitioner/Policy implications: This research can be used as a consideration for the company in policy making and as a basis for the company in decision making.Research limitation/Implication: The study’ results are expected to be a consideration in determining policies related to Islamic social reporting, especially law enforcement.